موازنة بين الإمامين السيوطي والبيضاوي حول معنى الهم من قوله تعالى:وَلَقَدْ هَمَّتْ بِه وَهَمَّ بِهَا - Ilham Syukri (UIN Fatmawati Sukarno Bengkulu, 2019)
The Qur'an is an eternal miracle, all its sides have the potential to carry varied meanings, such as the meaning of Al-hammu, so that they are not exhausted, explored and taken in wisdom both in terms of language and its other sides, although this is the case, there are scientists and researchers who are still able to strengthen one side and weaken the other side of meaning in the context of the meaning of al-hammu, but they not only rely on reason alone but with evidence and authentic propositions so meritorious in presenting new miracles in the Koran.